Unprecedented Homoleptic Bis‐Tridentate Iridium(III) Phosphors: Facile, Scaled‐Up Production, and Superior Chemical Stability. (26th July 2017) - Lin, Jun; Wang, Yang; Gnanasekaran, Premkumar; Chiang, Yu‐Cheng; Yang, Chun‐Chieh; Chang, Chih‐Hao; Liu, Shih‐Hung; Lee, Gene‐Hsiang; Chou, Pi‐Tai; Chi, Yun; Liu, Shun‐Wei
Abstract : Bis‐tridentate Ir(III) metal complexes are expected to show great potential in organic light‐emitting diode (OLED) applications due to the anticipated, superb chemical and photochemical stability. Unfortunately, their exploitation has long been hampered by lack of adequate methodology and with inferior synthetic yields. This hurdle can be overcome by design of the first homoleptic, bis‐tridentate Ir(III) complex [Ir(pzpyph)(pz H pyph)] (1 ), for which the abbreviation (pzpyph)H (or pz H pyph) stands for the parent 2‐pyrazolyl‐6‐phenyl pyridine chelate. After that, methylation and double methylation of1 afford the charge‐neutral Ir(III) complex [Ir(pzpyph)(pz Me pyph)] (2 ) and cationic complex [Ir(pz Me pyph)2 ][PF6 ] (3 ), while deprotonation of1 gives formation of anionic [Ir(pzpyph)2 ][NBu4 ] (4 ), all in high yields. These bis‐tridentate Ir(III) complexes2 –4 are highly emitted in solution and solid states, while the charge‐neutral2 and corresponding t ‐butyl substituted derivative [Ir(pzpy Bu ph)(pz Me py Bu ph)] (5 ) exhibit superior photostability versus the tris‐bidentate references [Ir(ppy)2 (acac)] and [Ir(ppy)3 ] in toluene under argon, making them ideal OLED emitters. For the track record, phosphor5 gives very small efficiency roll‐off and excellent overall efficiencies of 20.7%, 66.8 cd A −1, and 52.8 lm W −1 at high brightness of 1000 cd m −2 . These results are expected to inspire further studies on the bis‐tridentate Ir(III) complexes, which are judged to be more stable than their tris‐bidentate counterparts from the entropic point of view. Abstract : Homoleptic bis‐tridentate Ir(III) complexes are synthesized using a facile and simplified methodology. One monomethylated derivative (i.e., a t ‐butyl emitter) exhibits very small efficiency roll‐off and excellent efficiencies of 20.7%, 66.8 cd A −1, and 52.8 lm W −1, at a high brightness of 1000 cd m −2 .